Mortars from the Palace of Knossos in Crete, Greece: A Multi-Analytical Approach - Carvalho, Fernanda (2022)
ABSTRACT: The study of building materials constituting cultural heritage is fundamental to understand their characteristics and predict their behavior. When considering materials from archaeological sites, their characterization can provide not only relevant information for a broader understanding of the site and its importance and significance but can also increase knowledge about ancient materials and their performance. The Palace of Knossos is a very important archaeological site in the European history context, and its preservation benefits from the characterization of the constituent materials. Samples of mortars from this monument were collected under the scope of the H2020 HERACLES project, where a multi-analytical approach was chosen using established protocols for the different sample typologies. Instrumental techniques such as optical microscopy (OM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and simultaneous thermogravimetry and differential thermal analysis (TG-DTA) were used for the chemical, mineralogical, and morphological characterization of these mortar samples. The results indicate that the majority are lime mortars, both aerial and hydraulic, but gypsum-based mortars were also identified. Differences in the chemical composition of the samples in distinct areas of the monument allowed us to reflect on the variety of materials used in the construction of the Palace of Knossos.